Impact of ketogenic diets on cancer patient outcomes: a systematic review and meta-analysis - Zhang, Meiying; Zhang, Qing; Huang, Sheng; Lu, Yifu; Peng, Mengyun (Frontiers in Nutrition, 2025)
BackgroundThe ketogenic diet, characterized by high fat, moderate protein, and extremely low carbohydrate intake, has been widely used as a medical treatment for various conditions and has gained increasing attention in recent years due to its health benefits.ObjectivesThis study aims to investigate the effectiveness of a ketogenic diet on outcomes in cancer patients compared to conventional non-ketogenic diets.Materials and methodsStudies that assigned cancer patients to either a ketogenic diet or a standard diet control group were included. Two reviewers independently extracted and analyzed the data.ResultsThis meta-analysis revealed that the ketogenic diet significantly reduced fat mass, visceral fat, insulin levels, blood glucose, fatigue, and insomnia compared to a non-ketogenic diet while improving low-density lipoprotein (LDL) cholesterol, total cholesterol, thyroid-stimulating hormone (TSH) levels, protein uptake, ketosis events, emotional function, and social function. Furthermore, the ketogenic diet induced ketosis by increasing β-hydroxybutyrate levels.ConclusionThe ketogenic diet was found to improve cancer patients’ outcomes more effectively than non-ketogenic diets. Notably, C-reactive protein levels showed greater improvement when the intervention lasted more than 12 weeks, with a diet composition of 2–4% carbohydrates, 16–18% protein, and 80–85% fat.Systematic review registration(https://www.crd.york.ac.uk/PROSPERO/view/CRD42024553878) PROSPERO CRD4202455387.